Results of Two Non-Market Valuation Methods Used to Estimate Recreational Fishing in the Lakes Prespa Watershed - GRAZHDANI, Dorina (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).05, 2024)
Using both the travel cost and contingent valuation methods, a case study of Lakes Prespa was utilized to assess the demand functions for carp and non-carp angling separately. An on-site survey questionnaire was used to collect the data, which was completed in 2019. The results showed that when travel costs and bid amounts are higher or when anglers are traveling in larger groups, they travel less frequently. On the other hand, the number of trips is positively correlated with income, angling experience, the use of a motorized boat, the number of trips taken to other sites, and retirement. The mean daily consumer surplus values for carp and non-carp anglers were calculated to be €7.24 and €4.33, respectively, using the trip cost method, and €7.83 and €4.61 using the contingent valuation method. Regardless of the method of valuation utilized, carp anglers' consumer surplus was more than 1.7 times that of non-carp anglers, demonstrating that ordering in fish species values is robust to valuation methods. Furthermore, the convergent validity of the two techniques was identified. The results will help fisheries managers make more successful and resource-efficient fishing decisions, as well as policymakers justify funding initiatives targeted at managing and protecting this resource.